Comprehensive Physiology 1992
DOI: 10.1002/cphy.cp080125
|View full text |Cite
|
Sign up to set email alerts
|

Renal Blood Flow

Abstract: The sections in this article are: Measurement of Renal Blood Flow Total Renal Blood Flow Regional Cortical Blood Flow Medullary Blood Flow Renal Microcirculation Control of Renal Circulation Intrinsic Factors Extrinsic Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 534 publications
0
15
0
2
Order By: Relevance
“…First, PC MRI measurements of RBF were performed in the right renal artery only and assumed equal perfusion of both kidneys. However, this can be justified since kidney perfusion should amount to ≈20% of CO in healthy individuals and we measured a baseline RBF of 19±4.4% of CO. Secondly, we studied healthy volunteers and this limits the generalizability of our findings to CKD patients. Further studies in kidney disease require validation of the combined BOLD and PC MRI measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, PC MRI measurements of RBF were performed in the right renal artery only and assumed equal perfusion of both kidneys. However, this can be justified since kidney perfusion should amount to ≈20% of CO in healthy individuals and we measured a baseline RBF of 19±4.4% of CO. Secondly, we studied healthy volunteers and this limits the generalizability of our findings to CKD patients. Further studies in kidney disease require validation of the combined BOLD and PC MRI measurements.…”
Section: Discussionmentioning
confidence: 99%
“…After correction for background phase‐offset errors and aliasing, mean RBF (mL/s) was calculated in the right proximal renal artery using manual vessel segmentation in each cardiac phase (Figure D through F). Further RBF analysis assumed equal perfusion of both right and left kidneys . To make direct comparison between the radioisotope ERPF‐ and MRI‐derived RBF measurements possible, MR RBF was corrected for body surface area (according to Haycock) and hematocrit (Ht) to calculate a PC MRI‐based renal plasma flow (PC‐RPF).…”
Section: Methodsmentioning
confidence: 99%
“…22 In this setting, there is also an increased renal prostaglandin release that may counteract the effects of vasoconstrictors in the renal circulation, because the inhibition of prostaglandin synthesis accentuates renal vasoconstriction in these experimental models. 22 Therefore, it can be suggested that the activation of vasoconstrictor systems in the setting of gastrointestinal bleeding in humans may be more harmful to the cirrhotic kidneys compared with the normal kidneys be- Abbreviations: NSAIDs, nonsteroidal anti-inflammatory drugs; GIB, gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…At relatively high concentrations, Ang 1-7 and Ang IV exert modest renal vasodilation and natriuresis [967,[1060][1061][1062] . Although the putative receptors have not been cloned, recent studies indicate that the Ang [1][2][3][4][5][6][7] receptor is encoded by the MAS protooncogene [1068] . Although the putative receptors have not been cloned, recent studies indicate that the Ang [1][2][3][4][5][6][7] receptor is encoded by the MAS protooncogene [1068] .…”
Section: Intrarenal Angiotensin Receptorsmentioning
confidence: 99%